Mathematical reasoning program for the improvement of academic performance in basic education students - Ruiz Merino , Aurelio (2024)
This research aims to evaluate the impact of the application of a mathematical reasoning program on the academic performance of students in the first grade of secondary education of a public educational institution in San Juan de Lurigancho. A quasi-experimental design was used and we worked with a sample of 48 students, divided into a control group and an experimental group. A pretest and a posttest were applied to measure academic performance in mathematics and the mathematical reasoning program was applied to the experimental group for three months. The results showed a significant increase in academic performance in mathematics in the experimental group compared to the control group, demonstrating the effectiveness of the mathematical reasoning program in improving academic performance in this area.